2014
DOI: 10.1111/nicc.12095
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting and facilitating changes in caring for the intensive care unit patients' relatives

Abstract: Knowing these factors and sharing the experience of a successful change process can help others design processes appropriate to their site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Critical care nurses report that in addition to disrupting patient care, families also require the nurse to spend extra time and energy addressing their needs. Nurses view patient care as a priority and feel that they cannot meet both the needs of critically ill patients and their families (Kean & Mitchell, 2013;Mutair et al, 2013;Plakas et al, 2013;Riley et al, 2014;Zaforteza et al, 2014;McConnell & Moroney, 2014). Nurses described how they are overwhelmed by the continuous demands for information (Hart et al, 2013;Cappellini et al, 2014).…”
Section: Visitors As Helpersmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical care nurses report that in addition to disrupting patient care, families also require the nurse to spend extra time and energy addressing their needs. Nurses view patient care as a priority and feel that they cannot meet both the needs of critically ill patients and their families (Kean & Mitchell, 2013;Mutair et al, 2013;Plakas et al, 2013;Riley et al, 2014;Zaforteza et al, 2014;McConnell & Moroney, 2014). Nurses described how they are overwhelmed by the continuous demands for information (Hart et al, 2013;Cappellini et al, 2014).…”
Section: Visitors As Helpersmentioning
confidence: 99%
“…Nurses described how they are overwhelmed by the continuous demands for information (Hart et al, 2013;Cappellini et al, 2014). Multiple studies revealed that up to 87.5% of ICU nurses consider family presence a burden that increases their workload (Hart et al, 2013;Kean & Mitchell, 2013;Athanasiou et al, 2014;Cappellini et al, 2014;Riley et al, 2014;Zaforteza et al, 2014;McConnell & Moroney, 2014;Chapman et al, 2016). The additional task of addressing family needs increases the stress level of nurses already working in a stressful environment (Mutair et al, 2013;Plakas et al, 2013;Athanasiou et al, 2014).…”
Section: Visitors As Helpersmentioning
confidence: 99%
“…In the thematic analysis, we explored the transformation or reproduction of understandings, feelings, and power relations in ICU care‐giving (Zaforteza ; Zaforteza et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Zaforteza et al () describe how one unit in Spain attempted to attend more specifically to the needs of ICU relatives. The participatory action research (PAR) design specifically addresses the change process itself.…”
mentioning
confidence: 99%
“…Essentially, PAR is a quality improvement initiative but its philosophical origins and voluntary participation distinguish the methodology from a whole system approach to data collection and change implementation of quality improvement methods that favour technical evidence and non‐technical methods for improvement (culture, teams, leadership and learning from errors; Pronovost et al , ; Bion et al , ). Zaforteza et al () clearly demonstrate through their PAR methodology that the knowledge of power relations is sometimes as potent as the power of knowledge. Received knowledge (evidence, guidelines and standardisations) can be thwarted by positional authority and obstinately refuted.…”
mentioning
confidence: 99%